KORELASI DIGITAL HOARDING BEHAVIOR DAN MINDFULNESS PADA GURU DI JAKARTA - Amelia Aurora; Rahmah Hastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
A crucial phenomenon among middle-adult teachers indicates that 77.9% of participants exhibit a high level of digital hoarding behaviour. Digital hoarding is the tendency to collect and retain digital files excessively, often accompanied by emotional attachment and difficulty in deleting data that are no longer in use. Mindfulness, defined as full awareness of present-moment experience without judgement, functions as a protective factor in managing impulsive behaviours, including digital hoarding. This study aims to identify the correlational relationship between digital hoarding behaviour and mindfulness among middle-adult teachers in Jakarta. The research sample consisted of 149 teachers aged 40–50 years, selected through purposive sampling and assessed using the Indonesian versions of the Digital Hoarding Questionnaire (DHQ) and the Five Facet Mindfulness Questionnaire (FFMQ). Statistical analysis showed that the majority of respondents had high digital-hoarding scores (77.9%) and moderate mindfulness (79.2%), while only 3.4% achieved a high level of mindfulness. The correlation analysis yielded a significant negative relationship, with a Spearman’s rho value of –0.449 (p<0.001), indicating that the higher the mindfulness, the lower the digital hoarding behaviour. Further analysis found significant differences based on age and school level, though not by gender or the number of digital devices. These findings emphasise the importance of practical interventions such as mindfulness training and digital-data management workshops to reduce digital hoarding behaviour and improve teachers’ psychological well-being. It is suggested that educational institutions develop mentoring, coaching, and monitoring programmes to help teachers manage digital data and work-related stress. Future research is recommended to explore more deeply the influence of psychological and organisational factors. ABSTRAK Fenomena krusial pada guru dewasa madya menunjukkan bahwa 77,9% partisipan memiliki tingkat digital hoarding behavior yang tinggi Digital hoarding merupakan kecenderungan mengumpulkan dan mempertahankan file, digital secara berlebihan, seringkali, disertai keterikatan emosional dan kesulitan untuk menghapus data yang telah tidak terpakai.. Mindfulness, yang didefinisikan sebagai kesadaran penuh terhadap pengalaman saat ini tanpa menghakimi, berperan sebagai, faktor protektif dalam mengelola perilaku impulsif termasuk digital hoarding. Penelitian ini bertujuan untuk mengetahui, hubungan korelasi antara digital hoarding behavior dan mindfulness pada guru dewasa madya di, Jakarta. Sampel penelitian adalah 149 guru berusia 40-50 tahun, dipilih melalui, purposive, sampling dan diukur menggunakan Digital Hoarding Questionnaire, versi Indonesia (DHQ) serta Five, Facet Mindfulness Questionnaire, versi Indonesia (FFMQ). Analisis statistik menunjukkan mayoritas responden memiliki, skor digital hoarding tinggi (77,9%) dan mindfulness sedang (79,2%), sedangkan hanya 3,4% yang mencapai mindfulness tinggi.. Analisis korelasi menghasilkan hubungan negatif signifikan, dengan nilai, Spearman's tho sebesar -0,449 (p<0,001), menandakan bahwa semakin tinggi, mindfulness maka semakin rendah perilaku digital hoarding Analisis lanjutan me.nemukan perbedaan signifikan berdasarkan usia dan jenjang sekolah, namun tidak berdasarkan jenis kelamin atau jumlah perangkat digital Temuan ini menegaskan pentingnya intervensi praktis seperti, pe Jatihan mindfulness dan workshop manajemen data digital dalam upaya menurunkan digital hoarding behavior dan meningkatkan kesejahteraan psikologis guru diberikan Saran agar institusi pendidikan mengembangkan program pendampingan, coaching, dan monitoring untuk membantu guru mengelola data digital dan stres kerja Direkomendasikan penelitian selanjutnya agar lebih mengeksplorasi pengaruh faktor psikologis maupun organisasi secara lebih mendalam.